Some preliminary results of paleo-tsunami study in the coastal region of the Nghe An province, Vietnam - Trieu, Cao Dinh; Dung, Lai Van; Bach, Mai Xuan; Hung, Pham Nam; Trong, Cao Dinh; Tuan, Thai Anh; Quang, Phan Thanh; Hien, Pham Thi; Cuong, Nguyen Dac (Vietnam Journal of Marine Science and Technology, 2017)
In the coastal region of the Nghe An province, the geomorphology is characterized by appearances of fields of arca granosa with placura placenta and hills of placura placenta with arca granosa, namely: The hills of placura placenta with the arca granosa shells in the Quynh Van and Nghi Tien communes; the fields of arca granosa with the placura placenta: deep-seated in the Quynh Nghia, Dien Chau and along the Nghi Yen coast which have age of 4,500 - 4,300 yrs.; The appearance of the placura placenta-arca granosa shell’s fields and hills which do not originate from either marine transgression in the Holocene epoch, tectonic movement or artificiality; Our results suggest that there were three tsunami events occurring in the past during the periods of 4,500 - 4,300; 4,100 - 3,900 and 900 - 600 yrs., respectively in the region.